Clinical Characteristics of Anti-GABA-B Receptor Encephalitis - Zhu, Fei; Shan, Wei; Lv, Ruijuan; Li, Zhimei; Wang, Qun (Frontiers in Neurology, 2020)
Objective: Anti-GABA-B (gamma aminobutyric acid-B) receptor encephalitis is an autoimmune disease mediated by GABA-B-related antibodies. To fully understand the disease, we collected clinical data from patients with GABA-B receptor encephalitis and conducted an analysis to draw conclusions. Methods: All patients with GABA-B receptor encephalitis from the Neurology Department of Beijing Tiantan Hospital, affiliated with Capital Medical University, from August 2015 to September 2019 were accepted as study subjects. The clinical data of the patients were analyzed retrospectively and included the general demographic characteristics, clinical manifestations, and auxiliary examinations, including laboratory results, electroencephalograms (EEGs), brain magnetic resonance imaging (MRI), and positron emission tomography (PET-CT) results, as well as treatments. Results: From August 2015 to September 2019, 14 cases of anti-GABA-B receptor encephalitis were diagnosed. Among these patients, middle-aged and elderly men were the main demographic, with an average age of 52 years; moreover, the onset of the disease was relatively sudden, and the time from onset to diagnosis was ~1 month. The main clinical symptoms were frequent epileptic seizures, cognitive dysfunction, and mental behavioral disorders. In seven (50%) patients, the leukocyte in cerebrospinal fluid (CSF) were increased. Five (36%) patients had elevated cerebrospinal fluid protein. In most patients, the oligoclonal bands (83%) of CSF were positive, and 24 h IgG levels (92%) were increased. Anti-Hu or anti-Yo antibodies were positive in two (14%) patients. Tumor markers in 10 (71%) patients indicated that neuron-specific enolase, gastrin-releasing precursor, non-small cell lung cancer-related antigen, or carcinoembryonic antigen levels were increased. EEG results often indicated slow waves, sharp waves, or spike waves in temporal areas. Brain MRI always showed high T2 signals in the medial temporal lobe, hippocampus, and amygdala and swelling in the medial temporal lobe and hippocampus. PET-CT scans almost showed abnormal metabolism in the hippocampus and temporal lobe. Three (21%) patients who underwent systemic PET-CT showed hypermetabolism in pulmonary parenchymal nodules and enlargement of mediastinal lymph nodes. All patients underwent high-dose hormone therapy or immunoglobulin immunotherapy. After treatment, the symptoms of epilepsy, cognitive disorders, and mental behavioral disorders improved to varying degrees. However, one patient died of lung cancer. Conclusion: Anti-GABA-B receptor encephalitis mainly occurred in middle-aged and elderly men, and the disease onset was relatively sudden. Before disease onset, some patients experienced fever and non-specific respiratory symptoms, which mainly manifested as frequent epileptic seizures, cognitive dysfunction, and abnormal mental behavior. MRI and PET-CT revealed abnormal signals and local metabolism, respectively, in the temporal lobe. Moreover, the disease has a close relationship with lung cancer, which requires long-term follow-up observation.